Faktor-Faktor yang Mempengaruhi Cash Holding dengan Penghindaran Pajak sebagai Variabel Moderasi - Endang Ranitawati (Jurnal of Management and Social Sciences, 2024)
The purpose of this study is to empirically prove that cash holding can be influenced by the profitability of net working capital cash conversion cycle firm size and leverage either directly or indirectly mediated by tax availability in basic and chemical industrial manufacturing companies listed on the Indonesia Stock Exchange for the period 2018 - 2021. The measurement of the intervening tax avoidance variable uses the cash effective tax rate application, with purposive sampling in this study. Based on the existing criteria, a sample of 31 manufacturing companies in the basic and chemical industry sectors were obtained that were "listed" on the IDX for the period 2018-2021. and Firm Size significantly affect Cash Holding without being mediated by Tax Avoidance while Leverage can significantly affect Cash Holding mediated by Tax Avoidance for manufacturing companies in the basic and chemical industry sectors listed on the IDX for the period 2018 – 2021.